Towards monitoring the invisible threat: a global approach for tackling AMR in water resources and environment - Cutrupi, Francesca; Osinska, Adriana Dorota; Rahmatika, Iftita; Afolayan, Juwon Samuel; Vystavna, Yulija; Mahjoub, Olfa; Cifuentes, Jorge I.; Pezzutto, Denise; Muziasari, Windi (Frontiers in Water, 2024)
The global threat of antimicrobial resistance (AMR) is now increasingly recognized for the danger posed by its environmental spread. Aquatic environments and wastewater represent a significant diffusion and selection pathway for antibiotic resistance genes and bacteria. During a collaborative hackathon event, the "Innovation Workshop on Water Quality Monitoring & Assessment", held in September 2023, experts addressed four challenges related to water quality, including the challenge of globalisation AMR surveillance in water. This paper, derived from the workshop findings, proposes a globally adaptable model for antimicrobial resistance surveillance intended as an advance to improve future monitoring systems. The new framework aims to address significant challenges, such as the lack of standardised methodological approaches or lack of funding, coordination, and awareness across a short-, medium-and long-term plan, integrating sustainability concepts, extending participation and monitoring capacity of countries, and offering efficient solutions. This vision is first articulated by creating a technical committee that promotes awareness of antimicrobial resistance and develops a single data management and communication platform. Subsequently, by developing local, national, and international policies, centralised laboratories will be established at the regional level, and built based on existing realities. These laboratories will include facilities to make the management of analyses more efficient, from sampling to reporting the final result. In the long term, activities that allow the maintenance of the created framework and continuous technological development and advancement will be promoted. All will be achieved in collaboration with national and supranational bodies that are already addressing the issue at a global level.